THE EFFECT OF DIFFERENT TYPES OF PACKAGING FOR FISH SNACK QUALITY OF JELAWAT FISH (Leptobarbus hoevenii) DURING STORAGE - Suhardi '; Edison '; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study aims to determine the effect of using different types ofpackaging for fish snack quality of jelawat fish (Leptobarbus hovenii) duringstorage. The method used was experimental method, the experiment of makingfish snack jelawat fish. This research used non factorial randomized design wasthe use of a regular packing consists of three levels treatment. Use of LDPEpackaging (low density polyethylene) K1, HDPE packaging (High DensityPolyethylene) K2, PP packaging (Polypropylene) K3, storage period (group)consisting of four levels, namely L0 treatment (control), L15 (15 days), L30 (30days), L45 (45 days). 45 days was a type of HDPE packaging with characteristicvalue, odor, taste and texture (8.44), (8.54), (7.94), (8.42). While the chemicalanalysis value of water level, protein level, fat level, ash level and peroxide5.31%. 36.46%. 9.87%. 2.43% and 3.13% respectively.Keywords: packaging, fish snack, fish jelawat, storage period.